Call Processing Language (CPL) – A Tool for Creation of Internet Telephony Services by the End User - Pavel Segec; Tatiana Kovacikova (Communications - Scientific letters of the University of Zilina, 2008)
Creation and programming new services are considered as crucial for the Internet telephony (IPT). A number of protocols have been defined for IPT, however, one of them – the Session Initiation Protocol (SIP) seems to be the most relevant thanks to its manifold features. The SIP offers many forms that can be used for programming new IPT services. One of them is to use the SIP baseline protocol mechanisms, the other – to define extensions to the baseline SIP protocol specification (defining new headers, new methods). Finally, the dedicated programming tools such as a Call Processing Language – SIP CPL, Common Gateway Interface – SIP CGI, SIP-servlets, Java applets, Java API for Integrated Networks - JAIN APIs, Parlay can be used for creation of new IPT services. In this paper we focus on one of the SIP IPT features allowing creation and control of IPT services by the end user himself – CPL (Call Processing Language).